2018
DOI: 10.1080/10826084.2018.1441312
|View full text |Cite
|
Sign up to set email alerts
|

Cream of the Crop: Clinical Representativeness of Eligible and Ineligible Cannabis Users in Research

Abstract: Compared to ineligible cannabis users, eligible cannabis-using respondents were significantly younger, used cannabis more frequently, used alcohol less frequently, and were less likely to have a history of other drug use, a psychiatric diagnosis, or to have used psychiatric medication. Conclusions/Importance: Our findings indicate that eligible/pure cannabis users are not representative of typical cannabis users in the general community (i.e., ineligible users with polysubstance use and/or psychiatric diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Neurodevelopment and substance use risk are both influenced by many environmental and genetic factors (Creze et al, 2014; Fjell et al, 2015; Giedd et al, 2015; Gray and Squeglia, 2018; Jordan and Andersen, 2017), and how these factors may directly or indirectly influence neuromaturation trajectories and behavioral outcomes associated with the OFC will be further investigated in future work (Jernigan et al, 2018). Finally, and consistent with other studies (Rosen et al, 2018), participants in this study were relatively high-functioning healthy individuals (e.g. non-treatment seeking).…”
Section: Discussionsupporting
confidence: 89%
“…Neurodevelopment and substance use risk are both influenced by many environmental and genetic factors (Creze et al, 2014; Fjell et al, 2015; Giedd et al, 2015; Gray and Squeglia, 2018; Jordan and Andersen, 2017), and how these factors may directly or indirectly influence neuromaturation trajectories and behavioral outcomes associated with the OFC will be further investigated in future work (Jernigan et al, 2018). Finally, and consistent with other studies (Rosen et al, 2018), participants in this study were relatively high-functioning healthy individuals (e.g. non-treatment seeking).…”
Section: Discussionsupporting
confidence: 89%
“…Many prior neuroimaging studies of cannabis effects were restricted to dependent or heavy users and focused on the hippocampus and amygdala. Investigations of polysubstance cannabis users yield more generalizable results than studies of mono-users [106]: our HIV+ participants typified Hawaii's HIV population. Finally, to our knowledge this is the first study to examine RSFC in the context of both cannabis use and HIV.…”
Section: Discussionmentioning
confidence: 86%
“…While relationships between CAN use, fitness, and neuropsychological functioning were found, causality cannot be established due to the cross-sectional nature of this study; longitudinal studies, such as the Adolescent Brain Cognitive Development (ABCD) Study (https://abcdstudy.org/), are needed to clarify directionality of relationships. Recent research has indicated that CAN users included in studies such as this are not representative of the “typical” CAN user (e.g., lack of psychiatric co-morbidity, lower frequency of use; Rosen, Sodos, Hirst, Vaughn, & Lorkiewicz, 2018); therefore, these results may not generalize and/or may not reveal the true extent of relationships between CAN use and cognition in higher-risk groups. Even in domains where deficits were found, these were modest effects well below the typical 1.5 SD s associated with clinical significance; the real-world functional implications about such relative declines are lesser known, although CAN users have reported lower academic achievement (Fergusson & Boden, 2008; Horwood et al, 2010; Suerken et al, 2016), reduced salaries (Fergusson & Boden, 2008), and reduced life satisfaction (Fergusson & Boden, 2008; Grevensteine & Kroninger-Jungaberle, 2015).…”
Section: Discussionmentioning
confidence: 94%